The "Art of Memory" in the Jesuit Missions in Peru and China in the Late 16th Century - Hosne, Ana (Material Culture Review)

(untitled) (National Museums of Canada, 2012)
Abstract Abstract This article focuses on the “art of memory” in the Jesuit missions in colonial Peru and Ming China, especially through the works of José de Acosta (1540-1600) and Matteo Ricci (1552-1610). Jesuit education promoted training on how to enhance artificial memory in the colleges, and this interest in memory also circulated among the missions outside Europe. The Jesuits in Peru allowed and actually encouraged the use of the pre-Hispanic quipus—knotted-string devices—for memorization of doctrine and for confession. In turn, in the China mission, Ricci addressed the Chinese literati, presenting the Western Method of Memory or Xiguo Jifa (1596) as an ars memorativa from the West, especially when ars memorativa was intended as preparation for passing the civil examinations required to hold official posts in the Ming Empire. The purpose of this article is to answer why and how these Jesuits resorted to memory, and memory rules and techniques in these missions.